The Drivers of Housing Cycles in Spain - Rabanal, Pau (IMF Working Papers; Working Paper ;, 2009)
Since Spain joined the EMU, two main important factors behind the housing boom appear to be the decrease of nominal interest rates and demographic factors. In this paper we estimate a New Keynesian model of a currency area, using data for Spain and the rest of the EMU to study the importance of those factors. We also examine the role of different rigidities and find that labor market frictions are crucial to explain main features of the data. On the other hand, financial frictions that impose a collateral constraint on borrowing do not appear to be relevant.